A humanized 4-1BB-targeting agonistic antibody exerts potent antitumor activity in colorectal cancer without systemic toxicity - Lian-sheng Cheng; Yong-feng Cheng; Wen-ting Liu; Aolin Shen; Dayan Zhang; Tingjuan Xu; Wu Yin; Min Cheng; Xiaopeng Ma; Fengrong Wang; Qun Zhao; Xiaoli Zeng; et al. (Journal of Translational Medicine, 2022)
Abstract Background Colorectal cancer (CRC) is one of the most common malignancies and the patient survival rate remains unacceptably low. The anti-programmed cell death-1 (PD-1)/programmed cell death ligand 1 (PD-L1) antibody-based immune checkpoint inhibitors have been added to CRC treatment regimens, however, only a fraction of patients benefits. As an important co-stimulatory molecule, 4-1BB/CD137 is mainly expressed on the surface of immune cells including T and natural killer (NK) cells. Several agonistic molecules targeting 4-1BB have been clinically unsuccessful due to systemic toxicity or weak antitumor effects. We generated a humanized anti-4-1BB IgG4 antibody, HuB6, directed against a unique epitope and hypothesized that it would promote antitumor immunity with high safety. Methods The antigen binding specificity, affinity and activity of HuB6 were determined by enzyme-linked immunosorbent assay (ELISA), surface plasmon resonance (SPR), biolayer interferometry (BLI) and flow cytometry. The antitumor effects were evaluated in humanized mice bearing syngeneic tumors, and possible toxicity was evaluated in humanized mice and cynomolgus monkeys. Results HuB6 showed high specificity and affinity for a binding epitope distinct from those of other known 4-1BB agonists, including utomilumab and urelumab, and induced CD8 + T, CD4 + T and NK cell stimulation dependent on Fcγ receptor (FcγR) crosslinking. HuB6 inhibited CRC tumor growth in a dose-dependent manner, and the antitumor effect was similar with urelumab and utomilumab in humanized mouse models of syngeneic CRC. Furthermore, HuB6 combined with an anti-PD-L1 antibody significantly inhibited CRC growth in vivo. Additionally, HuB6 induced antitumor immune memory in tumor model mice rechallenged with 4 × 106 tumor cells. Toxicology data for humanized 4-1BB mice and cynomolgus monkeys showed that HuB6 could be tolerated up to a 180 mg/kg dose without systemic toxicity. Conclusions This study demonstrated that HuB6 should be a suitable candidate for further clinical development and a potential agent for CRC immunotherapy.